SYSTEM DESIGN ACCEPTANCE NEW STUDENTS OF PONDOK PESANTREN AL-MUKHLISHIN - Zainul Arham; H. Soetirto H. Soetirto. S, Drs, MA (Jurnal Sistem Informasi, 1998)
Pondok pesantren AL-MUKHLISHIN is one institution who are aware of the matter, so that more students are applying to the age of the institution aware of Pondok Pesantren AL-MUKHLISHIN, so the system acceptance of new students at the time of application so far is less effective and less efficient. With the system that created it can solve the problem.